POLIDEOXYRIBONUCLEOTIDE (PDRN): INNOVATIONS AND POTENTIAL IN TISSUE REGENERATION AND HEALING (International Seven Journal of Multidisciplinary, 2024)
Research on polideoxyribonucleotide (PDRN) highlights its significant potential in tissue regeneration and healing, emphasizing its importance in the fields of dermatology and regenerative medicine. PDRN is a biopolymer derived from salmon sperm DNA, recognized for its properties that facilitate wound healing, as well as its synergistic interactions with exosomes. These small extracellular vesicles play a crucial role in intercellular communication, and their combination with PDRN enhances the release of growth factors and other bioactive molecules that promote regeneration. Systematic reviews and clinical studies have demonstrated the efficacy of PDRN in various conditions, including tendinopathies, skin lesions, and bone healing. Data indicate that PDRN is safe, with no adverse effects reported in the reviewed studies, which increases its viability as a therapeutic option. Continued research into the molecular mechanisms underlying PDRN’s action is essential for standardizing dosages and treatment protocols, aiming to optimize its clinical applications. Furthermore, exploring combinations with other therapeutic agents and conducting multicenter studies are crucial for deepening the understanding of its effectiveness. In summary, PDRN represents an innovative and promising approach in the treatment of degenerative conditions and healing processes, signaling a positive future for regenerative medicine.